The impact of thyroid dysfunction on female reproductive function: a clinical case - Lіashuk Ruslana (ScienceRise: Medical Science, 2026)
The impact of thyroid dysfunction (primary and secondary hypothyroidism, Graves’ disease, functional autonomy) on female reproductive function is discussed. A clinical case of secondary hypothyroidism of adrenal origin affecting the development of infertility is presented. The aim of the study. To review the literature on the manifestations of reproductive function disorders and the assessment of thyroid status in women of reproductive age. Research results. In the case of thyroid hormone deficiency, there is a decrease in the gonadotropic function of the pituitary with the development of hyperprolactinemia and luteal phase insufficiency of the menstrual cycle. A reduction in the synthesis of sex steroid-binding globulin increases the level of free T4, which can cause symptoms similar to polycystic ovary syndrome. Hypothyroidism is a common cause of female infertility. In hyperthyroidism, women experience hyperestrogenism, leading to a reduction in follicle-stimulating hormone levels. Progesterone levels remain low due to reduced ovarian tissue sensitivity to luteinizing hormone in the context of follicle-stimulating hormone deficiency. Pregnancy is possible in women with Graves’ disease, but its course, in the absence of adequate treatment, is characterized by spontaneous miscarriage in 70% of patients. In primary hypothyroidism, the decreased production of thyroid hormones leads to increased secretion of thyroliberin, which further stimulates prolactin secretion, helping to explain the genesis of galactorrhea. It also reduces progesterone secretion by the ovaries. This results in the development of opsomenorrhea, amenorrhea, and infertility. One of the causes of central hypothyroidism may be adrenal-origin hyperandrogenism. Since hyperandrogenism blocks TSH secretion, the level of thyroid hormones in the blood decreases. Thyroliberin is activated, leading to the disruption of reproductive function. Conclusions. In cases of reproductive function disorders in women of reproductive age, it is essential to assess thyroid status and, if necessary, prescribe appropriate therapy. The issues discussed require further in-depth study, as they open up fundamentally new perspectives in the treatment of reproductive system dysfunctions in women